2021
DOI: 10.1007/s12666-021-02224-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Effects of Primary Stored Energy on Relaxation Behavior of High Entropy Bulk Metallic Glasses Under Compressive Elastostatic Loading

Abstract: This paper aims to show the effects of primary stored energy in high entropy bulk metallic glasses (HE-BMGs) on their relaxation behavior after elastostatic loading process. For this purpose, three HE-BMGs with different chemical compositions and primary stored energy were fabricated. Differential scanning calorimetry and nanoindentation tests were carried out to evaluate the relaxation enthalpy and microscopic mechanical characterization of alloys. The results showed that increase in the number of element typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In 2008, Lee et al reported that compressive loading of a Cu 65 Zr 35 bulk metallic glass at 90% of macroscopic yield stress for 12 h led to rejuvenation and improvement of the plastic strain from zero to 5.2% [22]. Following this work, numerous efforts were made to explore the effect of elastostatic compression conditions on the deformation behavior of various BMG systems [6,[23][24][25][26]. For example, Tong et al reported that a threshold stress should be applied for rejuvenation in thermos-mechanical creep [27].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Lee et al reported that compressive loading of a Cu 65 Zr 35 bulk metallic glass at 90% of macroscopic yield stress for 12 h led to rejuvenation and improvement of the plastic strain from zero to 5.2% [22]. Following this work, numerous efforts were made to explore the effect of elastostatic compression conditions on the deformation behavior of various BMG systems [6,[23][24][25][26]. For example, Tong et al reported that a threshold stress should be applied for rejuvenation in thermos-mechanical creep [27].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Our research team is involved in high-quality publications and has extensive knowledge to translate the experiments. [ 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 ] To date to the best of our knowledge, there are no proper reports available on marine actinobacteria Nocardiopsis sp. from which the melanin pigment is extracted.…”
Section: Introductionmentioning
confidence: 99%